Inside Back Cover: Bandgap Engineering through Controlled Oxidation of Polythiophenes (Angew. Chem. Int. Ed. 7/2014). Issue 7 (23rd January 2014) - Wei, Sujun; Xia, Jianlong; Dell, Emma J.; Jiang, Yivan; Song, Rui; Lee, Hyunbok; Rodenbough, Philip; Briseno, Alejandro L.; Campos, Luis M.
<x xml:space="preserve">Abstract</x> Hypofluorous acid is a potent and selective oxidizing agent that can react with thiophene‐containing polymers to change their optoelectronic properties. As L. M. Campos and co‐workers report in their Communication on page 1832 ff., the thiophene units are converted into nonaromatic thiophene‐1, 1‐dioxides, thereby resulting in materials with increased electron affinity and a smaller optical bandgap. The image depicts the fast chemical transformation of the conjugated polymers.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>